Lost and Found - Oliver Jeffers (London, United Kingdom HarperCollins Publishers, 2006)
New cover reissue of this magical story from award-winning international bestselling picture book creator, Oliver Jeffers There once was a boy...and one day a penguin arrives on his doorstep. The boy decides the penguin must be lost and tries to return him. But no one seems to be missing a penguin. So the boy decides to take the penguin home himself, and they set out in his row boat on a journey to the South Pole. But when they get there, the boy discovers that maybe home wasn't what the penguin was looking for after all
Keywords: Circle Time Book - Relationships / Teamwork /Conflict Resolution -- Circle Time Book - Relationships / Teamwork /Conflict Resolution